2015
DOI: 10.1016/j.jaridenv.2015.02.022
|View full text |Cite
|
Sign up to set email alerts
|

A climate change projection for summer hydrologic conditions in a semiarid watershed of central Arizona

Abstract: Potential climate change impacts on summer precipitation and subsequent hydrologic responses in the southwestern U.S. are poorly constrained at present due to a lack of studies accounting for high resolution processes. In this investigation, we apply a distributed hydrologic model to the Beaver Creek watershed of central Arizona to explore its utility for climate change assessments. Manual model calibration and model validation were performed using radar-based precipitation data during three summers and compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

5
5

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 53 publications
0
32
0
Order By: Relevance
“…(4) RegCM4.3 downscaling of the HadGEM2-ES model underestimated precipitation by 15% during the historical period as compared with the station data. (5) RegCM4.3 simulations were applied to SWAT without a bias correction, which has advantages [10,86] and disadvantages [87]. (6) SWAT was forced with a single RCM (RegCM4.3 forced with HadGEM2-ES) and a single emission scenario (RCP 8.5).…”
Section: Discussionmentioning
confidence: 99%
“…(4) RegCM4.3 downscaling of the HadGEM2-ES model underestimated precipitation by 15% during the historical period as compared with the station data. (5) RegCM4.3 simulations were applied to SWAT without a bias correction, which has advantages [10,86] and disadvantages [87]. (6) SWAT was forced with a single RCM (RegCM4.3 forced with HadGEM2-ES) and a single emission scenario (RCP 8.5).…”
Section: Discussionmentioning
confidence: 99%
“…Recent developments used in this work include a method for ingesting time-variable vegetation parameter values (Vivoni, 2012) and a parallelization method based on subdomain partitioning of the channel network . In previous studies, tRIBS has shown good performance with respect to soil moisture and temperature, ET, and streamflow measurements (e.g., Hawkins et al, 2015;Mahmood & Vivoni, 2011;Méndez-Barroso et al, 2014;Pierini et al, 2014;Xiang et al, 2014).…”
Section: Model Description Including Channel Transmission Lossesmentioning
confidence: 96%
“…2013analyzed the open-access outputs of 14 GCM-RCM combinations from the ENSEMBLES project to identify those exhibiting the best performance in terms of representing the intra-annual variability of precipitation and temperature in the present climate for the seven study sites of the precursor European project. For each study site, the selected set of climate model data was validated using the E-OBS dataset, a high-quality pan-European gridded observational dataset of daily precipitation and temperature (Haylock et al, 2008). The models (and their acronyms: ECH-RCA, ECH-REM, ECH-RMO, and HCH-RCA) selected for the Rio Mannu site are listed in Table 2.…”
Section: Hydrologic Modelsmentioning
confidence: 99%